Abu Zayd’s Hermeneutics Approach to The Qur’an: A Refutation - Metsra Wirman (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2024)
It is important to note that the modern Qur’an studies has been under the influence of western thoughts. There have been a number of approaches to the Qur’an which treated the Islamic traditions unfair and to some extent skeptically. This paper, tries to analyze Abu Zayd’s thought on interpreting the al-Qur’an that was solely to apply a methodology of literary criticism and attempts to refute his thought in the light of hermeneutics and modern approaches to the Qur’an. A Qur’an texts accordingly were regarded as the cultural product so that in his view the Qur’an like other literary texts which are undergoing socio-politico-historical courses; it is inclusive to literary criticism. He was believing in the validity of Wilhem Dilthey’s methodology on textual analysis, his discourse on Qur’an studies was the product of Western hermeneutics that is certainly irrelevant when it comes to be applied to analyze the Qur’an since it does not undergo any distortion all the time. Therefore, the conclusion of this paper was Nasr Hamid Abu Zayd’s hermeneutics approach was appropriate for the Bible instead of the Qur’an.